Development of Marketing Strategy and se of Human Capital Assets for Effective Management in Agricultural Sector Enterprise Activities - LYSENKO, Kateryna A.; MECHIKOVA, Maria N.; LEMANOVA, Polina V. (Journal of Advanced Research in Law and Economics, 2017)
The paper deals with the peculiarities of general marketing strategy development, the goals of Agricultural Sector (hereinafter AS) and use of human capital assets considering social and economic aspects of the industrial enterprises. It substantiates the ways of marketing strategy, which allow considering the strategy as an internal support for business planning. The authors suggest that at the marketing strategy development the necessity of choice of possible solutions should be taken into account considering development of human capital assets. The content of the AS marketing development strategy is investigated as well as the main stages of the strategy development implying cooperation of the AS components on the market.